Transformasi Komunikasi Organisasi Pemerintah Kota Medan dengan Pendekatan Islam dalam Mewujudkan Masyarakat Maju dan Kondusif - Amril; Kholil, Syukur (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This research aims to explore the transformation of organizational communication of the Medan City Government by integrating Islamic values to create an advanced and conducive society. The research method used is a qualitative approach with a phenomenological method, which focuses on a deep understanding of the subject's experience in a natural context. Primary data were collected through non-participant observations, while secondary data were obtained through relevant literature reviews. Data analysis follows the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn, with data validity tested through triangulation techniques. The results of the study show that the transformation of communication based on Islamic values in the Medan City Government has strengthened transparency, public participation, and public trust in the government. However, there are challenges in maintaining inclusivity and increasing community involvement in the decision-making process. On the other hand, the use of digital technology provides a great opportunity to expand the reach of communication and strengthen the relationship between the government and the community.